2016
DOI: 10.3390/polym8060224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polyplex Formation on the Performance of Star-Shaped Polycationic Transfection Agents for Mammalian Cells

Abstract: Genetic modification ("transfection") of mammalian cells using non-viral, synthetic agents such as polycations, is still a challenge. Polyplex formation between the DNA and the polycation is a decisive step in such experiments. Star-shaped polycations have been proposed as superior transfection agents, yet have never before been compared side-by-side, e.g., in view of structural effects. Herein four star-shaped polycationic structures, all based on (2-dimethylamino) ethyl methacrylate (DMAEMA) building blocks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…The zeta potential was measured for the polyplexes as a function of the N/P ratio (ratio of polymer N to DNA P), Table 1. Hepes-buffered glucose solution (HBG) was used as matrix for polyplex formation, because in our hands, this buffer originally proposed by Van Gaal et al [30] had previously been more efficient in transfecting mammalian cells that the commonly used unbuffered 150 mM NaCl [31]. As expected, the zeta potential of the polyplexes increases with increasing N/P ratio.…”
Section: Physicochemical Characterization Of the Polyplexesmentioning
confidence: 61%
See 2 more Smart Citations
“…The zeta potential was measured for the polyplexes as a function of the N/P ratio (ratio of polymer N to DNA P), Table 1. Hepes-buffered glucose solution (HBG) was used as matrix for polyplex formation, because in our hands, this buffer originally proposed by Van Gaal et al [30] had previously been more efficient in transfecting mammalian cells that the commonly used unbuffered 150 mM NaCl [31]. As expected, the zeta potential of the polyplexes increases with increasing N/P ratio.…”
Section: Physicochemical Characterization Of the Polyplexesmentioning
confidence: 61%
“…It is generally considered difficult to uncouple the two effects. However, in a recent paper [31], we have shown that independent of the N/P ratio the cytotoxicity of the transfection cocktail depends strongly on the absolute amount of polymer added. This phenomenon has been obscured in most previous investigations by the fact that the N/P ratio is adjusted by keeping the pDNA amount constant while increasing that of the polycation.…”
Section: Optimization Of the Standard Transfection Protocol For Jurkamentioning
confidence: 83%
See 1 more Smart Citation
“…The Freitag group polymerized 20 “arms” of pDMAEMA off a silsesquioxane core and used this star polymer to deliver pDNA or siRNA, obtaining approximately 50% knockdown from siRNA delivery, and 10-50% transfection efficiency with 40-100% viability using pDNA [21]. This group also recently reported 13% transfection efficiency of primary T cells using this material with cell viability of 80% [22]. Most recently, the Stephan group reported a nanoparticle formulation with a poly(β-amino ester) core for DNA condensation and an antibody-conjugated polyglutamic acid shell for receptor-mediated uptake that was successfully used for in vitro and in vivo gene delivery to primary murine T cells, achieving ~3% transfection efficiency in vitro and ~1.5% in vivo [23].…”
Section: Introductionmentioning
confidence: 99%
“…Lactate and glucose concentrations were quantified with commercial kits (UV-method) from R-Biopharm AG (Darmstadt, Germany). EGFP expression was measured as previously described by flow cytometry [31] or spectrophotometrically [30]. In HEK293trans cells, EGFP was also quantified in cell lysates.…”
Section: Analyticsmentioning
confidence: 99%